PERLINDUNGAN HUKUM PADA BANK TERHADAP PENERIMAAN JAMINAN PERORANGAN DALAM PENYALURAN KREDIT - Herina, Herina; Svinarky, Irene (SCIENTIA JOURNAL, 2021)
In credit financing, it is inseparable from the provision of material guarantees that are used as credit guarantees. The purpose of the request for collateral is to secure credit and minimize risk if the debtor does not fulfill his obligations. The use of individual guarantees is also carried out as additional collateral for the provision of debtor credit. In providing individual guarantees, banks accept third parties as guarantors only based on the credibility and reputation of the guarantor itself. The bank does not perform an appraisal or prior to the amount and wealth owned by the guarantor because there are no objects belonging to the guarantor that are bound to the creditor to fulfill the debtor's obligations if the debtor defaults. Based on the above background, this research was conducted with the aim of describing the mechanism for receiving individual guarantees at banks. This study uses an empirical juridical approach. The results of this study will show the form of legal protection for banks in receiving individual guarantees in order to avoid running away from the responsibility of the guarantor.